UPAYA SEKRETARIAT DAERAH DALAM PENINGKATAN DISIPLIN APARATUR SIPIL NEGARA (ASN) DI KABUPATEN KAMPAR TAHUN 2022 - Zulgaheni, Zahwa; Nasution, Hazqon Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The Kampar Regency Government, particularly the Regional Secretariat, implements employee discipline to improve the quality of ASN. The purpose of this research is to describe the factors influencing the indiscipline of State Civil Apparatus (ASN) in the Regional Secretariat of Kampar Regency in 2022 and to describe the efforts of the Kampar Regency Government in enhancing the discipline of State Civil Apparatus (ASN) in the Regional Secretariat of Kampar Regency in 2022. The method used in this research is qualitative, with a descriptive research approach, and the research location is in Kampar, Riau Province, specifically at the District Secretariat Office. This research uses two types of data, namely primary data and secondary data. The data collection techniques used are interviews and documents, while the data analysis technique involves describing phenomena, classifying them, and examining how the emerging concepts are interconnected. The findings obtained in this study are that there are 3 indicators of work discipline, namely Time Discipline, which includes implementing an electronic attendance system, a 5% deduction from TPP per day if. Regulatory Discipline refers to adherence to working hours, work ethics, standard operating procedures (SOP), and Responsible Discipline pertains to the accuracy of tasks performed by ASN, along with sanctions imposed on ASN who are not accountable for their performance. Keywords: Time discipline, rule discipline, responsibility discipline, fingerprint, accuracy